Analisis Pemasaran Semangka : (Studi Kasus pada Desa Lombang Kecamatan Bantang-batang) - Dody Tri K; Dewi Wulansari (Prosiding Seminar Nasional Ilmu Ekonomi dan Akuntansi, 2024)
The aim of this research is to find out marketing channels, marketing margins, as well as watermelon marketing efficiency. Respondents were taken using a simple random method and for marketing institution respondents using snowball sampling), where the data was initially small and then became large by following the marketing flow from farmer to final consumer, there were 40 farmers (respondents) and 4 traders (respondents). ). Data analysis uses quantitative descriptive, the data collected is analyzed to determine the marketing channels, marketing magin and efficiency obtained by each marketing institution. The results of this research are 3 (three) marketing channels for watermelon, namely marketing channel I farmer - consumer, marketing channel II farmer - retailer - consumer, and marketing channel III farmer - collector - retailer - consumer. The largest total marketing margin is in marketing channel III with a margin of Rp. 4500 with marketing efficiency of 8.7%. Marketing channel I is the most efficient marketing channel because it does not involve institutions marketing.